Growth of peaches at three altitudes in the Santander mountains of Northeastern Colombia (Bioagro, 2024)
A study was conducted in the high tropics in the province of Pamplona, Colombia, with the objective of evaluating the growth of peach, Jarillo variety, under three different altitudes (1670, 1870, and 2170 masl). A total of eight trees were sampled per altitude for the purposes of this study. Ten fruits were taken from the middle third, and their mass was measured as follows: fresh and dry from the fruit and fruit pulp, pulp-seed ratio, and the roundness index during the three stages of development after defoliation. A multivariate analysis of variance and a nested longitudinal mixed model were employed to analyze the total fresh mass from three altitudes. The simple effects of altitude and the phenological stages and their interaction were found to be significant when the nested structure of the random effects, fruits nested in trees, and trees in altitudes were incorporated. The effects of time and altitude demonstrated a significant interaction for all variables. In all cases, 1670 masl was the altitude which had the highest fresh mass and the pulp-seed relationship, which it allowed a higher percentage of pulp from harvested fruits for agro-industrial processes. The pattern of relationship between fruit-associated variables as a function of days after defoliation was explained using a second-order polynomial regression model.
Keywords: Fruit roundness index; mixed nested longitudinal model; Prunus persica